2012
DOI: 10.3390/su4092210
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Attitudes and Environmental Behavior—Which Is the Horse and Which Is the Cart?

Abstract: Abstract:The present article challenges the prevailing perception in the field of environmental education that acquisition of environmental behavior is an ultimate goal of the educational process, in comparison to acquisition of environmental attitudes, which is perceived as a minor goal. The article presents a compilation of results obtained from two studies that shed new light on the relationship between influences on environmental attitudes and influences on environmental behavior. The results suggest that:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0
18

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(95 citation statements)
references
References 71 publications
3
74
0
18
Order By: Relevance
“…The findings regarding the studied grassland site align well with previous findings by Eilam and Trop [40,41]. These studies compared the two constructs of attitude and behaviour between children and adults, in regard to concrete issues occurring at the present time.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The findings regarding the studied grassland site align well with previous findings by Eilam and Trop [40,41]. These studies compared the two constructs of attitude and behaviour between children and adults, in regard to concrete issues occurring at the present time.…”
Section: Discussionsupporting
confidence: 78%
“…LaPiere's findings were reiterated in further studies [29,38]. By the mid-20th century, researchers came to regard behaviour as an outcome of situational rather than dispositional influences [39][40][41][42].…”
Section: Literature Reviewmentioning
confidence: 93%
“…This is substantiated by the work of Caldwell (2011) when he revealed that respondents in Ontario, Canada showed concern about the local environmental issues. Also Eilam and Trop (2010) also revealed that respondents possess positive attitude towards the environment but the strategies required for influencing attitude are different from those required for influencing attitudes are different from those required for influencing behaviours.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Regardless of the determinants of behavior, analyses of perception tend to show that the range of uses and values depends on the context [38,39] implying that knowledge, social recognition and even social demand with respect to ecosystem services vary according to both the type of actor and the area concerned [40]. In order to be adapted, policies must therefore be defined and implemented according not only to the degree of anthropization (as noted by Schneiders et al [26]) but also to the scales and contexts [6].…”
Section: Need To Study Perception Diversitymentioning
confidence: 99%